KEMAMPUAN MENULIS DONGENG MENGGUNAKAN TEKNIK SIMAK DAN TULIS SISWA KELAS VII SMP NEGERI 27 PADANG - Rahmi, Silvia; Muhardis, Muhardis; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2014)
The problem of this research was the studentsâ ability in writing tales by using listening and writing technique in class VII of SMP Negeri 27 Padang. This research was designed for describing the studentsâ ability in writing tales by using listening and writing technique in class VII of SMP Negeri 27 Padang. This was a quantitative research which used descriptive method. Based on the results of the research some conclusions were drawn. First, the studentsâ ability in writing tales by using listening and writing technique for the first indicator was more than adequate (72,3) in which their average score was in the range of 66-75%. Second, the studentsâ ability in writing tales by using listening and writing technique for the second indicator was very good(90,4) in which their average score was in the range of 86-95%. Third, the studentsâ ability in writing tales by using listening and writing technique for the third indicator was more than adequate (75,2) in which their average score was in the range of 66-75%. Fourth, the studentsâ ability in writing tales by using listening and writing technique for the fourth indicator was very good (91,4) in which their average score was in the range of 86-95%. Fifth, in the general, the average score of the studentsâ ability in writing tales by using listening and writing technique was good (82,3) in which their average score was in the range ofÂ  76-85%.